2008
DOI: 10.1007/s10511-008-9000-1
|View full text |Cite
|
Sign up to set email alerts
|

Transient phenomena in cosmic ray intensity during extreme events

Abstract: In the present work an analysis has been made of the extreme events occurring during July 2005. Specifically, a rather intense Forbush decrease was observed at different neutron monitors all over the world during 16 July 2005. An effort has been made to study the effect of this unusual event on cosmic ray intensity as well as various solar and interplanetary plasma parameters. It is noteworthy that during 11 to 18 July 2005 the solar activity ranged from low to very active. Especially low levels occurred on 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…This may be due to the fact that as the strength of the magnetic field increases the cosmic-ray charged particles experience more Lorentz force, as a result of which these charged particles are deflected from their original path, which creates a decrease in CRI. Our finding is in a good agreement with the findings of Agarwal and Mishra (2008), who have found that the CRI tends to decrease with increase of IMF B. In our study, we have noticed that the decrease in CRI takes place on the same day or one day after the increase in IMF B.…”
Section: Cri and Imfsupporting
confidence: 93%
“…This may be due to the fact that as the strength of the magnetic field increases the cosmic-ray charged particles experience more Lorentz force, as a result of which these charged particles are deflected from their original path, which creates a decrease in CRI. Our finding is in a good agreement with the findings of Agarwal and Mishra (2008), who have found that the CRI tends to decrease with increase of IMF B. In our study, we have noticed that the decrease in CRI takes place on the same day or one day after the increase in IMF B.…”
Section: Cri and Imfsupporting
confidence: 93%